An Analysis of Student Pedagogical Skills in Applying Mathematics Learning in Elementary Schools - Ramdhan Witarsa Witarsa; Lussy Midani Rizki (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study is to describe the pedagogical skills of students in applying mathematics learning in elementary schools. The pedagogical skills studied focused on skills in making lesson plans and implementing learning. The method used was descriptive quantitative research method. The research sample used was 13 students of the 5th semester elementary school teacher education study program. The results showed that the students' pedagogical skills were in the good category with an average score of 81.11%. Recommendations that can be given are the need for students to be accompanied on an ongoing basis starting from the stage of making lesson plans, implementation, to evaluation when the implementation of mathematics learning is simulated in the classroom.